Positive moods are all alike? Differential affect amplification effects of ‘elated’ versus ‘calm’ mental imagery in young adults reporting hypomanic-like experiences - Vannucci, C; Bonsall, MB; Di Simplico, M; Cairns, A; Holmes, EA; Burnett Heyes, S (Springer Nature, 2022)
Positive mood amplification is a hallmark of the bipolar disorder spectrum (BPDS). We need better understanding of cognitive mechanisms contributing to such elevated mood. Generation of vivid, emotionally compelling mental imagery is proposed to act as an ‘emotional amplifier’ in BPDS. We used a positive mental imagery generation paradigm to manipulate affect in a subclinical BPDS-relevant sample reporting high (n = 31) vs. low (n = 30) hypomanic-like experiences on the Mood Disorder Questionnaire (MDQ). Participants were randomized to an ‘elated’ or ‘calm’ mental imagery condition, rating their momentary affect four times across the experimental session. We hypothesized greater affect increase in the high (vs. low) MDQ group assigned to the elated (vs. calm) imagery generation condition. We further hypothesized that affect increase in the high MDQ group would be particularly apparent in the types of affect typically associated with (hypo)mania, i.e., suggestive of high activity levels. Mixed model and time-series analysis showed that for the high MDQ group, affect increased steeply and in a sustained manner over time in the ‘elated’ imagery condition, and more shallowly in ‘calm’. The low-MDQ group did not show this amplification effect. Analysis of affect clusters showed high-MDQ mood amplification in the ‘elated’ imagery condition was most pronounced for active affective states. This experimental model of BPDS-relevant mood amplification shows evidence that positive mental imagery drives changes in affect in the high MDQ group in a targeted manner. Findings inform cognitive mechanisms of mood amplification, and spotlight prevention strategies targeting elated imagery, while potentially retaining calm imagery to preserve adaptive positive emotionality.